The painless eye: Neurotrophic keratitis in a child suffering from hereditary sensory autonomic neuropathy type IV - Sethi, Aditya (Indian J Ophthalmol, 2020)
Hereditary sensory autonomic neuropathy (HSAN) is a group of inherited disorders (total 5 types) that are associated with sensory dysfunction and varying degrees of autonomic dysfunction. HSAN type IV (HSAN-IV) or congenital insensitivity to pain and anhidrosis (CIPA) is a rare genetic disorder inherited in an autosomal recessive manner. We report a case of this very rare genetic disease in a 3-year-old girl child, born to a family in north India with ocular features of neurotrophic keratitis. The diagnosis was made clinically based on the hallmark features of insensitivity to pain and temperature, anhidrosis, self-mutilating behavior with multiple recurrent oral ulcers, nasal bleeds, multiple trophic ulcers over joints, and decreased intellect.